Mosque mosaic - Khairunisa Shamsuri (2015)
A sequential image of Islamic geometric patterns which are driven by social and cultural influences, particularly that pertaining to the religion Islam. It serves to explore the arbitrariness and disparity of individuals that are still largely interconnected with the core of Islam. Metaphorically our lives are interwoven like a spider’s web with the nucleus being our closest relationship which guides and leads us. Symbolized through the representation of the repeated central designs, every individual build is seen as a fragment to a bigger picture where communities of various cultures flourish and yet stay strong of their roots